SEROPREVALENCE OF TRANSFUSION TRANSMISSIBLE INFECTIONS AMONG BLOOD DONORS AT A TERTIARY CARE TEACHING HOSPITAL IN AJMER, RAJASTHAN: A 5 YEAR STUDY - MEENA, GOKUL CHAND; Beelwal, Dinesh; TAILOR, SHASHI BHUSHAN; SUNARIA, RAVI KANT (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to study the seroprevalence of TTIs (transfusion transmissible infections) among blood donors from the records (June 2017–May 2022) at blood center, JLN Hospital and associated group of Hospital, Ajmer, Rajasthan. Methods: A cross-sectional study was carried out over a period of 5 years from June 2017 to May 2022. Serum samples were screened for hepatitis B virus (HBV), hepatitis C virus (HCV) (III generation ELISA), antibodies to human immunodeficiency virus (HIV) Type 1 and 2 (IV generation ELISA kits), Syphilis and Malaria parasite using modified Treponema pallidum hemagglutination test and rapid card test, respectively. Results: A total of 75,034 healthy donors were included out of which majority of donors were male (97.4%). The overall seroprevalence of HIV, HBV, HCV, Syphilis, and Malaria were 0.07%, 0.71%, 0.06%, 0.29%, and 0.05%, respectively. Conclusion: Methods to ensure a safety blood supply should be encouraged. The increase in public awareness regarding voluntary blood donation, meticulous donor screening, counseling and use of highly sensitive tests can help in reducing the risk of TTIs.